2016
DOI: 10.1186/s12879-016-1964-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of cryptococcal meningitis in HIV seronegative children in Beijing, China, 2002–2013

Abstract: BackgroundData regarding HIV-seronegative pediatric patients with cryptococcal meningitis (CM) have been very limited.MethodsWe retrospectively reviewed non-HIV-infected in patients with CM from January 2002 through December 2013 in Beijing Children’s Hospital. Records of the all patients were obtained and compared.ResultsThe 34 children had a median age of 5.6 years. Most of the patients were male (67.6 %). Only 23.5 % of the cases had identifiable underlying diseases. The sensitivity of the CSF cryptococcal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 30 publications
2
28
1
Order By: Relevance
“…Intense headache, vomiting and confusion were present in this case as well as in the Colombian children study where the most frequently reported symptoms were headache (78.1%), fever (68.8%), nausea and vomiting (65.6%), confusion (50%) and meningeal signs (37.5%). Except for the fever and meningeal signs not observed, clinical findings in this case are consistent with those found by other authors [3,[6][7][8]10].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Intense headache, vomiting and confusion were present in this case as well as in the Colombian children study where the most frequently reported symptoms were headache (78.1%), fever (68.8%), nausea and vomiting (65.6%), confusion (50%) and meningeal signs (37.5%). Except for the fever and meningeal signs not observed, clinical findings in this case are consistent with those found by other authors [3,[6][7][8]10].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding Colombian minors, Lizarazo et al reported that almost half (46.3%) of the patients in their study did not have underlying conditions. Other reports about this mycosis in underage patients in Brazil, Cuba, China and Taiwan indicate that in most cases there were no risk factors associated [3,[6][7][8]. Almost 20% of patients diagnosed with cryptococcosis in many health care facilities are clinically non-immunocompromised and there is evidence that within this population, innate or acquired immunodeficiencies may underlie [6,9].…”
Section: Discussionmentioning
confidence: 97%
“…X-linked hyper IgM syndrome is a genetic defect in the gene encoding CD40 ligands on activated CD4 T cells, and is required for normal B cells activation [ 90 , 91 , 93 ]. C. neoformans infections are also linked to a total absence of B cells, such as in Burton’s agammaglobulinaemia in non-HIV patients [ 94 , 95 ]. These examples show that B cells and antibodies play an important role in controlling cryptococcal infection.…”
Section: Antibody-mediated Immunity Against Cryptococcal Infectionmentioning
confidence: 99%
“…CM is associated with high rates of mortality and morbidity, and as with other CNS fungal infections, Therefore, CM has a severe economic impact on healthcare systems [2,3]. A paediatric study of CM from China reported that the majority of patients were apparently normal, and only 23.5% had identifiable underlying conditions [4]. Paediatric cryptococcosis has been reported in both HIV-negative and -positive patients [5,6], however other immunocompromising medical conditions are usually seen in HIV-negative patients [5].…”
Section: Introductionmentioning
confidence: 99%